2006
DOI: 10.1111/j.1742-1241.2005.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

Restenosis after carotid endarterectomy

Abstract: Multiple randomised trials over the last decade for both symptomatic and asymptomatic carotid stenosis have proven the efficacy of carotid endarterectomy (CE) in reducing the risk of stroke. The long-term patency of the carotid artery after CE is an important factor in the success of the operation. The incidence of recurrent carotid stenosis (excluding residual lesions) ranges from 1 to 37% with only 0-8% of patients having restenosis-related symptoms (1). Generally, recurrent carotid stenosis is attributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 43 publications
1
40
0
3
Order By: Relevance
“…Restenosis of a CEA is relatively rare, occurring in a range of 1-37% of patients, with only 0-8% having restenosis-related symptoms in one clinical trial. 1 In recent trials, the fi gures show an incidence rate of restenosis to be closer to 6-14%, which equates to an average annual restenosis or occlusion rate of 1.5-4.5%. A review of this also revealed a risk of recurrent stenosis of 10% in the fi rst year, 3% in the second, and 2% in the third, suggesting that the rate of restenosis may not be linear throughout the follow-up period.…”
Section: Carotid Artery Endarterectomymentioning
confidence: 99%
See 3 more Smart Citations
“…Restenosis of a CEA is relatively rare, occurring in a range of 1-37% of patients, with only 0-8% having restenosis-related symptoms in one clinical trial. 1 In recent trials, the fi gures show an incidence rate of restenosis to be closer to 6-14%, which equates to an average annual restenosis or occlusion rate of 1.5-4.5%. A review of this also revealed a risk of recurrent stenosis of 10% in the fi rst year, 3% in the second, and 2% in the third, suggesting that the rate of restenosis may not be linear throughout the follow-up period.…”
Section: Carotid Artery Endarterectomymentioning
confidence: 99%
“…1 With the improvement in diagnostic imaging and surgical techniques, CEAs are now being performed more than at any other time in the history of the operation. 1 CEAs are usually performed on symptomatic patients with a greater than 70% stenosis. Clinical trials have proven CEA to be benefi cial in helping to reduce the number of strokes today.…”
Section: Carotid Artery Endarterectomymentioning
confidence: 99%
See 2 more Smart Citations
“…Thin film nitinol (TFN) is a novel material worth considering for developing a low-profile endovascular device [13]. Vacuum sputter deposition process for thin film nitinol is the preferred fabrication method because of the precise controllability of the deposition process and the consistency of the quality of the films [14]. Furthermore, thin film nitinol can be used in small calibre vascular systems as it exhibits superelastic property at body temperature, which improves the device apposition to the vascular wall compared to any synthetic fabric (like polyethylene terephthalate micronet) that typically has wrinkles or permanent deformation.…”
Section: Introductionmentioning
confidence: 99%